Very-High-Energy γ-Ray Observations of the Blazar 1ES 2344+514 with VERITAS - Ahnen, M. L.. (2017)
We present very-high-energy γ-ray observations of the BL Lac object 1ES 2344+514 taken by the Very Energetic Radiation Imaging Telescope Array System (VERITAS) between 2007 and 2015. 1ES 2344+514 is detected with a statistical significance above background of 20.8σ in 47.2 hours (livetime) of observations, making this the most comprehensive very-high-energy study of 1ES 2344+514 to date. Using these observations the temporal properties of 1ES 2344+514 are studied on short and long times scales. We fit a constant flux model to nightly- and seasonally-binned light curves and apply a fractional variability test, to determine the stability of the source on different timescales. We reject the constant-flux model for the 2007-2008 and 2014-2015 nightly-binned light curves and for the long-term seasonally-binned light curve at the > 3σ level. The spectra of the time-averaged emission before and after correc- tion for attenuation by the extragalactic background light are obtained. The observed time-averaged spectrum above 200 GeV is satisfactorily fitted (χ*2 /NDF = 7.89/6) by a power-law function with index Γ = 2.46 ± 0.06 stat ± 0.20 sys and extends to at least 8 TeV. The extragalactic-background-light-deabsorbed spectrum is adequately fit (χ*2 /NDF = 6.73/6) by a power-law function with index Γ = 2.15 ± 0.06 stat ± 0.20 sys while an F-test indicates that the power-law with exponential cutoff function provides a marginally-better fit (χ 2 /N DF = 2.56/5) at the 2.1σ level. The source location is found to be consistent with the published radio location and its spatial extent is consistent with a point source.